Characteristics of the Protein Complexes and Pores Formed by Bacillus cereus Hemolysin BL - Jessberger, Nadja (Toxins (Basel), 2020)
Bacillus cereus Hemolysin BL is a tripartite toxin responsible for a diarrheal type of food poisoning. Open questions remain regarding its mode of action, including the extent to which complex formation prior to cell binding contributes to pore-forming activity, how these complexes are composed, and the properties of the pores formed in the target cell membrane. Distinct complexes of up to 600 kDa were found on native gels, whose structure and size were primarily defined by Hbl B. Hbl L1 and L2 were also identified in these complexes using Western blotting and an LC-MS approach. LC-MS also revealed that many other proteins secreted by B. cereus exist in complexes. Further, a decrease of toxic activity at temperatures ≥60 °C was shown, which was unexpectedly restored at higher temperatures. This could be attributed to a release of Hbl B monomers from tight complexation, resulting in enhanced cell binding. In contrast, Hbl L1 was rather susceptible to heat, while heat treatment of Hbl L2 seemed not to be crucial. Furthermore, Hbl-induced pores had a rather small single-channel conductance of around 200 pS and a probable channel diameter of at least 1 nm on planar lipid bilayers. These were highly instable and had a limited lifetime, and were also slightly cation-selective. Altogether, this study provides astonishing new insights into the complex mechanism of Hbl pore formation, as well as the properties of the pores.